2020
DOI: 10.1038/s41419-020-2286-6
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the ER-stress-regulator MANF triggers progressive outer hair cell death and hearing loss

Abstract: The non-conventional neurotrophic factor mesencephalic astrocyte-derived neurotrophic factor (MANF) is an endoplasmic reticulum (ER)-resident protein that promotes ER homeostasis. MANF has a cytoprotective function, shown in the central nervous system neurons and pancreatic beta cells. Here, we report that MANF is expressed in the hair cells and neurons and in selected non-sensory cells of the cochlea and that Manf inactivation triggers upregulation of the ER chaperones in these cells. However, Manf inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…www.nature.com/scientificreports/ astrocyte-derived neurotrophic factor (MANF). In this genetic mouse model, ER stress is associated with loss of synapses in the cochlea, accompanied by progressive hair-cell death and hearing loss 18 . The findings that MANF is cytoprotective in neurons and that Manf inactivation is associated with loss of synapses in the inner ear suggests that the UPR may act similarly in the brain and auditory sensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ astrocyte-derived neurotrophic factor (MANF). In this genetic mouse model, ER stress is associated with loss of synapses in the cochlea, accompanied by progressive hair-cell death and hearing loss 18 . The findings that MANF is cytoprotective in neurons and that Manf inactivation is associated with loss of synapses in the inner ear suggests that the UPR may act similarly in the brain and auditory sensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…A link between UPR-mediated neurodegeneration in the brain, hair-cell loss, and cochlear synaptopathy was suggested by recent work in mice deficient for the ER-stress-regulator mesencephalic astrocyte-derived neurotrophic factor (MANF). In this genetic mouse model, ER stress is associated with loss of synapses in the cochlea, accompanied by progressive hair-cell death and hearing loss 16 . The findings that MANF is cytoprotective in neurons and that Manf inactivation is associated with loss of synapses in the inner ear suggests that the UPR may act similarly in the brain and auditory sensory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a MANF deficiency becomes detrimental when accompanied by gene mutations that predispose to HL, which act by intensifying ER dyshomeostasis. On the basis of these observations, the authors of this study concluded that MANF might serve as a therapeutic candidate for protection against HL induced by stressors that target the ER machinery [36].…”
Section: Hearing Lossmentioning
confidence: 86%